Design and Implementation of Buck Converter for Fast Charging with Fuzzy Logic - Indhana Sudiharto; Moch. Igam Rahadyan; Ony Asrarul Qudsi (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
This research presents a battery charger design that can charge faster than using a PWM type solar charge controller (SCC). SCC is often operated when the battery capacity is 80% so that the charging current that can be provided is only 10% to 20% of the battery capacity. The battery charging method applied in this study uses the principle of fast charging by adjusting the value of the current and the output voltage value of the buck converter. Fast charging has its own characteristic, obviously, the charging rate that is greater than the usual charging method, which is up to 1C of the battery capacity. The principle of fast charging in this study uses the constant current / constant voltage method. This converter is designed with the ability to produce current by the charging rate of 1C from a 12Ah battery capacity of 12 A and an output voltage of 16.8 V. To ensure that the output of the converter matches the setpoint, the duty cycle value is adjusted using fuzzy control. Based on the results obtained from the simulation, the control of this study obtained an output current 12  Amperes with error ripple current around 8.3%. The SOC on this battery increased by 75.74% in 45 minutes.Keywords: fast charging, fuzzy, buck convreter